2017
DOI: 10.1093/pm/pnx067
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Long-Term Treatment Outcome of Children and Adolescents with Disabling Chronic Pain

Abstract: The results of this study support the long-term effectiveness of intensive interdisciplinary pain treatment and indicate that it can interrupt pain chronification. Future research is warranted to investigate why some of the adolescents did not show improvement and to allow for a more individualized treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 24 publications
3
46
1
8
Order By: Relevance
“…It is of utmost importance to introduce comprehensive pain care early in the pediatric age group to optimize patients' QOL now and in the future. 349…”
Section: Unique Issues Related To Pediatric Pain Managementmentioning
confidence: 99%
“…It is of utmost importance to introduce comprehensive pain care early in the pediatric age group to optimize patients' QOL now and in the future. 349…”
Section: Unique Issues Related To Pediatric Pain Managementmentioning
confidence: 99%
“…Other LTx programs may use these data to guide chronic pain management in their cohorts and consider similar multidisciplinary approaches or intensive inpatient therapy to improve transplant‐related outcomes while minimizing long‐term opioid use. Recent studies have shown that not only have these methods been more effective in treating pain while limiting the use of opioids, but they can also reduce costs associated with pain management . For patients with chronic pain, current recommendations emphasize trying other types of prescription pain medication before initiating opioid therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that not only have these methods been more effective in treating pain while limiting the use of opioids, but they can also reduce costs associated with pain management. [37][38][39][40][41] For patients with chronic pain, current recommendations emphasize trying other types of prescription pain medication before initiating opioid therapy. 20 More research is needed to determine the long-term safety and efficacy of opioid-sparing approaches to chronic pain in the LTx population.…”
Section: Discussionmentioning
confidence: 99%
“…B. durch Arbeitsausfall der Eltern, aber auch Kosten für die Familien (Fahrten, Therapiekosten etc.) [8,9]. Auf lange Sicht lässt sich sehr schwer abschätzen, welche Kosten entstehen, wenn die Betroffenen evtl.…”
Section: Folgen Chronischer Schmerzenunclassified